Population Study of Javan Green Peafowl (Pavo muticus muticus Linneaus 1758) with Three Different Methods in Baluran National Park, East Java Indonesia - Jawardi Budi Hernowo (Department of Forest Resources Conservation and Ecotourism - IPB University, 1997)
The green peafowl (Pavo muticus) has been nominated an a globally threatened bird species (ICBP). It is protected bird in Indonesia and a new species as mentioned in the red data book (IUCN). The present distribution of the bird in Java is irregular and locally. A few information about the bird population and the data in many cases are not available. Research was conducted in Baluran national park, East java. it was aimed to obtaining the case of concusing method population size, structure and mx ratio of Java green peafowl. Three different methods were used: call count transect method, consentration count and capture mark recapture. Call count method with transect lines ir appropriate on consering of the green peafowl population from sample area indicating in relatively better related to the number (118 bird in 1200 ha). However, population structure was dominated by adult bird 70% - 80 %. The bird mx ratio was 1 male : females, indicated that bird lived in polygamous system.